Studi Perencanaan Pengelolaan Lahan di Sub DAS Cisadane Hulu Kabupaten Bogor - Nining Puspaningsih (Institut Pertanian Bogor (IPB University), 1999)
The research area is an upper watershed and is a land culture for the peasant its self. Then in the plan of land management have to participate the social economic life of community in this area. The alternative plan of land management based on the erosion prediction (A) and to enable erosion (T). The land management and the techniques of land conservation have to arranged if A value more high then T value. This problem happened because the negative impact of land changes. These values must be manipulated in order to A value less than T value. The selection of CP value have to less then and equal with the T/RKLS ratio or the CP maximum value. The must of part of area research have A value more high then T value and plan alternative is rice field, dry field and mixed field with system tumpang sari, agro tourism and protection forest areas.